Epidemiological profile of accidents by snakes in the municipality of Palmas, 2007-2017 (Research, Society and Development, 2022)
Objective: To describe the epidemiological profile of accidents by snakes in the city of Palmas, Tocantins, from 2007 to 2017. Methodology: Epidemiological study of the descriptive type based on data on accidents by venomous animals from the Department of Informatics of the Unified Health System in the period from 2007 to 2017. Results: 400 cases of snakebites were reported in the municipality of Palmas between 2007 and 2017. The most affected age group was 20-39 years of age (41.25%), with a predominance of males (73 .75%), of mixed race/color (74%) and with low education. Almost 100% were cured. The occurrence of snakebites of the bothrops genus was predominant and increasing. Most snakebites were considered mild or moderate (95.75%), and 4.25% were severe. Conclusion: The higher prevalence of snakebites in the city of Palmas in mixed-race and low-education populations evokes the need to look at social vulnerabilities and to improve the program for the control of Accidents by Venomous Animals to broaden the understanding and recommendations for the practice and education related to snakebites in this population.